Manajemen Interaksi Pembelajaran Pendidikan Tinggi Jarak Jauh untuk Menguatkan Pembelajaran Mendalam: Studi Literatur - Laurenty, Fretycia (Proceeding of Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2025)
This literature review synthesizes findings from more than thirty-five reputable international studies to examine how learning interaction management in Distance Higher Education contributes to strengthening deep learning within the context of Society 5.0. Grounded in the Community of Inquiry (CoI), Transactional Distance Theory (TD), and recent meta-analyses, the review maps interaction forms, determinants, contextual challenges, and technological opportunities. Evidence demonstrates that high-quality instructional design, strong teaching presence, digital competence, and institutional digital governance effectively enhance cognitive presence and support deeper learning. Unique challenges in Asian contexts—including passive learning behaviors, invisible learners, hierarchical norms, and cognitive overload—limit optimal interaction. This review provides strategic pedagogical and managerial recommendations to optimize learning interaction aligned with technological innovations within Society 5.0.